Isolasi Dan Karakterisasi α-amilase Isolat Bakteri Amilolitik Asidofilik Dari Taman Nasional Rawa Aopa Watumaohai - Sapto Raharjo; Ardiansyah Ardiansyah; Agus Chahyadi (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2008)
Isolation and characterization α-amylase acidophilic amylolytic bacteria isolate from Rawa Aopa Watumohai National Park has been carried out. The aims of these studies are to know the characteristics of acidophilic amylolytic bacteria isolate, the optimum concentration of substrate and temperature α-amylase activity yielded, and specific activity in each enzyme purification steps. Activity of α-amylase was measured with DNS (Dinitrosalisilic acidI) method at λ 550 nm and the rate of protein enzyme was measured with Biuret method at λ 540 nm. The content of this research were obtained the isolate bacteria TR 1 which higher amylolytic activity is the colonies are pale-yellow with convexelevated, undulate, bacill sel, and negative Gram. The maximum activity and protein content obtained with (NH4)2SO4 extracted at 60% (w/v). The specific activity of α-amylase in crude extract was 0.038 U/mg enzyme, after extracted with (NH4)2SO4 60% (w/v) was 0.146 U/mg enzyme with purification fold 3.8, and after dialysis was 0.255 U/mg enzyme with purification fold 3.8, respectively. The optimum concentration of substrate (amylose) was 1.25% (w/v) and the optimum incubation temperature was 45oC.Keywords : Rawa Aopa Watumohai National Park, acidophilic amylolytic bacteria, α-amilase